Gang change and evolutionary theory - Ayling, Julie (Crime, law and social change, 2011)
While most street gangs are temporary and disorganized, some have institutionalized, and a number of these show signs of evolving into more serious criminal enterprises, becoming more networked, technologically savvy and internationalized, less visible, more predatory and sometimes more violent. The boundaries that researchers have drawn between gangs and other types of criminal groups, particularly organized crime, are becoming blurred. Understanding why this is happening is crucial to planning effective responses. This article suggests that evolutionary theory, involving processes of variation, selection and replication, would constitute a valuable tool for this purpose. Using an evolutionary framework would enable the application of a longitudinal perspective to the microsocial level of analysis, the gang itself, which until now has not had as much attention as other levels of analysis in gang research. Taking inspiration from evolutionary theories in organizational sociology and economics, this article explores how evolutionary theory might be used to understand gang change and locate gangs within evolutionary sequences. It argues that adopting an evolutionary perspective will improve the capacity of law enforcement agencies to focus scarce resources where they are most needed and to plan and implement successful interventions.